Effectiveness of mobile robots collecting vital signs and radiation dose rate for patients receiving Iodine-131 radiotherapy: A randomized clinical trial - Li, Dan; Gao, Dingwei; Fan, Suyun; Lu, GangHua; Jiang, Wen; Yuan, Xueyu; Jia, Yanyan; Sun, Ming; Liu, Jianjun; Gao, Zairong; Lv, Zhongwei (Frontiers in Public Health, 2023)
Objective Patients receiving radionuclide 131I treatment expose radiation to others, and there was no clinical trial to verify the effectiveness and safety of mobile robots in radionuclide 131I isolation wards. The objective of this randomized clinical trial was to evaluate the effectiveness and safety of mobile robots in providing vital signs (body temperature and blood pressure) and radiation dose rate monitoring for patients receiving radionuclide therapy. Methods An open-label, multicenter, paired, randomized clinical trial was performed at three medical centers in Shanghai and Wuhan, China, from 1 April 2018 to 1 September 2018. A total of 72 participants were assigned to the group in which vital signs and radiation doses were both measured by mobile robots and conventional instruments. Intergroup consistency, completion rate, and first success rate were the primary effectiveness measures, and vital sign measurement results, the error rate of use, and subjective satisfaction were secondary indicators. Adverse events related to the robot were used to assess safety. Results Of the 72 randomized participants (median age, 39.5; 27 [37.5%] male participants), 72 (100.0%) completed the trial. The analysis sets of full analysis set, per-protocol set, and safety analysis set included 72 cases (32 cases in Center A, 16 cases in Center B, and 24 cases in Center C). The consistency, completion rate, and first success rate were 100% (P = 1.00), and the first success rates of vital signs and radiation dose rate were 91.7% (P = 1.000), 100.0% (P = 0.120), and 100.0% (P = 1.000). There was no significant difference in vital signs and radiation dose rate measurement results between the robot measurement group and the control group (P = 0.000, 0.044, and 0.023), and subjective satisfaction in the robot measurement group was 71/72 (98.6%), compared to 67/72 (93.1%) in the control group. For safety evaluation, there was no adverse event related to the mobile robot. Conclusion The mobile robots have good effectiveness and safety in providing vital signs and radiation dose rate measurement services for patients treated with radionuclides.